Parvovirus B19 in the practice of obstetrician-gynecologist - О. А. Бурка; И. В. Сидорова (Publishing House TRILIST, 2018)
Parvovirus B19 (PV B19, infectious erythema, "fifth disease", "slap syndrome") is a pathogenic human single-stranded DNA virus of the family of parvovirus, which breeds in erythroid precursor cells and causes them to die. The replication of the virus occurs mainly in the precursor cells of the erythroid group (erythroblast), megacarocytes and macrophages of the bone marrow, the spleen, as well as placental endothelial cells, in the tissues of the myocardium, liver, lungs, kidneys and synovial membranes of the fetus. People with genetically absent R-antigen (1 out of 200 thousand people) are resistant to infection with PV B19. The risk of primary infection during pregnancy depends on the epidemiological situation and ranges from 1.5 to 14.5%. In 70% of infected pregnant women there will be no clinical manifestations of the disease. The risk of vertical transmission of parvovirus B19 is 35%. Up to 85% of all cases of fetal vesicles are nonimmune vesicles in the fetus. Three main mechanisms are associated with its development: intrauterine anemia, heart failure and hypoproteinemia. In the case of damage to parvovirus B19, nonimmune vesicle in the fetus develops to 27% of cases, most often - at gestational age of 10-20 weeks. It is recommended that pregnant women who are in contact with patients with parvovirus B19 patients or who have similar clinical manifestations of the disease are consulted for the purpose of determining their immune status. Diagnosis on parvovirus B19 to perform in the case of the development of non-immune vesicles in the fetus or intrauterine fetal death. ML "DILA" offers the European quality of research - immunoblot IgM and IgG. A wide selection of biological material for PCR-research on parvovirus V19 (blood, saliva, chorion and other types of biomaterials: oral smear, liquor, amniotic fluid, bone marrow biopsy). Possibility of differentiation of immunoglobulins of mother and newborn. High accuracy of quantitative research results: sensitivity 92.2%, 100% specificity.